L’extravagance du berger extravagant de Charles Sorel (1627-1634) : un concept heuristique de la création fictionnelle au XVIIe siècle - Anne-Elisabeth Spica (Carnets)
Le Berger extravagant’s plot, a novel published by Charles Sorel in 1627, is based on the adventures of a young man who has decided to live his life as the shepherds in pastoral narratives. The novel, entitled Anti-Novel in the second edition of 1633, mirrors the processes of its genre. Thus, the character of the extravagant hero suggests a permanent off-centre point of view which creates a better perspective in considering what should be fiction. How does telling the adventures of an extravagant allow the pragmatic refoundation of the novel around the year 1630 in France?